ANALISIS PENGARUH MODAL SENDIRI, MODAL LUAR, VOLUME USAHA, DAN TINGKAT PERPUTARAN PIUTANG TERHADAP SISA HASIL USAHA - Gaviota Gilda Putri; Bambang Sunarko; Retno Widuri (Faculty of Economics and Business Universitas Jenderal Soedirman, 2016)
The purpose of this research was to describe the development of cooperatives, to investigate the influence of own capital, loan capital, bussines volume, and receivable turn over on added value of cooperatives. The samples of this research were financial statements in Sejati Mulia business cooperatives, Ceger Jaya busiess cooperatives, and Tunas Jaya business cooperatives from 2004-2014. The method of this research was purposive sampling. The technique of data analysis used was linier multiple regression with classical assumption. The result indicated that own capital,loan capital, bussines volume, and